2023
DOI: 10.1002/ijgo.14710
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of placenta accreta spectrum with nomogram combining radiomic and clinical factors: A novel developed and validated integrative model

Abstract: Objective: To develop and validate a clinicoradiomic nomogram based on sagittal T2WI images to predict placenta accreta spectrum (PAS). Methods: Between October 2016 and April 2022, women suspected of PAS by ultrasound were enrolled. After taking into account exclusion criteria, 132 women were retrospectively included in the study. The variance threshold SelectKBest and the least absolute shrinkage and selection operator were applied to select radiomic features, which was further used to calculate the Rad-scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The significance of our research's Nomogram predictive model is primarily focused on the occurrence of IPH caused by placenta accreta. Recent studies [18][19][20] have reported the significance of related Nomogram predictive models for placenta accreta spectrum. They found Nomogram predictive model constructed with certain MRI imaging features and clinical characters have value in the prediction of placenta accreta spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of our research's Nomogram predictive model is primarily focused on the occurrence of IPH caused by placenta accreta. Recent studies [18][19][20] have reported the significance of related Nomogram predictive models for placenta accreta spectrum. They found Nomogram predictive model constructed with certain MRI imaging features and clinical characters have value in the prediction of placenta accreta spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating patients with PAS is of paramount importance, but identifying the many risk factors involved can be challenging. Recent studies have developed clinical prediction models based on clinical data, highlighting the potential for timely risk stratification of the target population [26,27]. A prospective cohort study constructed a model including four key variables (loss of clear zone, abnormal placental lacunae, placental bulge and bladder wall interruption) was shown to reliably predict presence and severity of PAS.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Hu et al 1 titled “Prediction of placenta accreta spectrum with nomogram combining radiomic and clinical factors: A novel developed and validated integrative model”. The authors showed that the clinicoradiomic model, combining the intraplacental T2‐hypointense bands (ITHB) visually assessed by the radiologist and radiomics features, had balanced diagnostic performance in training and test cohorts in differentiating between placenta accreta spectrum (PAS) and normal placenta.…”
mentioning
confidence: 99%